Flight Re-timing Models to Improve the Robustness of Airline Schedules: Khusnul Novianingsih - Team, Support (Thai Journal of Mathematics, 2016)
We study a problem on improving the robustness of airline schedules. A schedule is robust if the schedule can minimize the effect of flight delays in day-to-day operations. We improve the robustness of flight schedules by re-timing departure time of flights. We derive stochastic optimization models to change departure times of flights in which the feasibility of both aircraft and crew connections are maintained. We solve the models using flight delay simulation. The computational results show that the re-timing flights can improve the robustness of aircraft routings significantly.